Genetic Engineering Materials Bank of The National Center for Biotechnology - Sarsen, A.; Saginova, M.; Mukanov, B.; Aktayeva, S.; Akishev, Zh.; Mussakhmetov, A.; Kiribayeva, A.; Baltin, K.; Silayev, D.; Khassenov, B. (Eurasian Journal of Applied Biotechnology, 2020)
For the development of science-intensive technologies in biology, biotechnology and medicine, it is necessary to store valuable DNA samples: genes of enzymes, antigens, proteins for various purposes, and DNA loci in a depository. Storing DNA is inexpensive, and having such a depository will reduce the time spent on research in basic and applied science. The genetically engineered materials bank has been formed at the National center for biotechnology. Now, the bank has 88 samples of cloned genes of enzymes, antigens, proteins and diagnostically significant loci. Plasmid vectors with cloned genes are stored at a temperature -20°С. Besides competent cells of Escherichia coli strain DH5α were transformed with vectors and recombinant strains were isolated. Recombinant strains carrying the required plasmid vectors are stored for cryopreservation at a temperature -80°С.